Structure and Magnetic Properties of Two Discrete 3d‐4f Heterometallic Complexes. Issue 32 (24th August 2020) - Yang, Panpan; Yu, Shui; Quan, Lixia; Hu, Huancheng; Liu, Dongcheng; Liang, Yuning; Li, Bo; Liang, Fupei; Chen, Zilu
Abstract: Two discrete 3d–4f heterometallic complexes [Co III Dy III (CH3 CN)0.5 (L 1 )3 (NO3 )3 ] (1 ) and [Ni2 II Dy III (EtOH)(L 2 )4 (NO3 )2 Cl] ⋅ CH3 CN (2 ) were obtained from the reactions of 8‐hydroxyquinoline (HL 1 ) or 2‐methyl‐8‐hydroxyquinoline (HL 2 ) with their corresponding metal salts. Complex 1 presents a dinuclear structure with the Dy(III) and Co(II) ions linked by three phenolic oxygen atoms from three (L 1 ) − ligands. Complex 2 presents a triangular trinuclear structure with the two Ni(II) ions and one Dy(III) ion consolidated by one chloride ligand and four phenolic oxygen atoms from four (L 2 ) − ligands. Their χ M T versus T plots show different profiles with obvious ferromagnetic interactions between the metal ions in 2 . Both complexes exhibit slow magnetic relaxation behaviours, but with obvious different features. It revealed a cooperatively regulating effect of ligand and transition metal ions on the structures and magnetic properties. Abstract : Two discrete 3d–4f heterometallic complexes of dinuclear Co III Dy III and triangular trinuclear Ni2 II Dy III were successfully prepared using the ligands of 8‐hydroxyquinoline and 2‐methyl‐8‐hydroxyquinoline, respectively. The Co(III) ion in the Co III Dy III complex is at low spin state with its all magnetic properties from the Dy(III) ion. The dynamic magnetic measurements revealed that both complexes exhibit slow magnetic relaxation but with obvious difference. It revealed a synergetic tuning effect of ligand and transition metal ions on the structure and magnetic properties.